Coupling pathogen recognition to innate immunity through glycan-dependent mechanisms - Davicino, Roberto Carlos (2011)
Innate immune cells have evolved to sense microbial pathogens through pattern recognition receptors (PRRs), which interact with conserved pathogen-associated molecular patterns (PAMPs) to convey microbial information into immune cell signaling and activation events. PRRs also recognize endogenous damage-associated molecular patterns (DAMPs), including alarmins released during microbial invasion, initiation of autoimmune inflammation or tumor growth. In spite of the well-established role of Toll-like receptors (TLRs) in mediating these recognition events, compelling evidence supports a central function for lectin-glycan interactions in promoting microbial sensing and evoking immune responses. Here we discuss the role of glycans and lectins (particularly galectins) in mediating microbial recognition and initiation of innate immune responses. Both microbes and host cells are sources of glycan-containing information which is, at least in part, decoded by endogenous glycan-binding proteins or lectins, including C-type lectins, siglecs and galectins. Although C-type lectins and siglecs can recognize microbial glycans when expressed on the cell surface of innate immune cells, galectins mainly function as soluble mediators that bridge microbial or host glycans to amplify or attenuate immune responses. Galectins are widely expressed in host cells and play important roles during different steps of infection such as pathogen recognition, invasion and resolution. In addition, recent studies report the presence of conserved 'galectin-like' domains in certain pathogens including helminths and protistan parasites, suggesting that they could also serve as potential virulence factors that influence the outcome and course of infection. Understanding the role of lectin-glycan interactions and the relevance of PRR or PAMP glycosylation in microbial recognition might contribute to the design of novel prophylactic and therapeutic strategies.